Training of Development of Inquiry-Based and Project-Based Chemistry Learning Design for Chemistry & Science Teachers - Sulistina, Oktavia; Widarti, Hayuni Retno; Habiddin, Habiddin; Herunata, Herunata; Yahmin, Yahmin; Hasanah, Samudra Mutiara; Zahirah, Dhea Fairuza (Universitas Negeri Malang, 2023)
Abstrak – Nowadays, the demands of curriculum are increasing in achieving better standards of learning process. The low ability of chemistry and science teachers in developing inquiry-based and project-based learning designs is a problem that must be solved. The ability of teachers in making learning designs is one of the pedagogic competencies and professional competencies that teachers must master in their professional development. So there is a need for community service or training to teachers to facilitate this. The method of implementing this community service activity includes the presentation of material on inquiry-based and project-based chemistry learning design, discussion and question and answer, and assistance to teachers in developing the learning design, until teachers are able to make inquiry-based and project-based chemistry learning tools (including lesson plans, teaching materials, and assessment instruments). The result of the training activities was an increase in the knowledge and skills of chemistry and science teachers regarding making inquiry-based and project-based learning designs. Enthusiasm and curiosity in developing knowledge about learning design make this training activity useful for participants.Keywords: Learning Design; Inquiry; Project; Teacher; Training